Spatiotemporal characteristics of interday temperature fluctuations across the Loess Plateau of China - Xiangyu Guo; Yunqiang Wang; Lei Wang; Hui Sun; Haibo Du; Zhengfang Wu; Hongshi He; Weijian Zhou (International Journal of Climatology, 2021)
Interday temperature fluctuations (ITFs) have a series of direct and visible impacts on human productivity, daily life, and some rapidly occurring processes in the Earth's critical zones. The Loess Plateau of China (LPC) is characterized by Chinese continental monsoon climate and fragile ecological environment, and thus, is sensitive to ITFs. To evaluate the spatiotemporal distribution of the ITF frequency and level, and the related large‐scale circulation background, we collected daily temperature data from 53 meteorological stations in the LPC for 1961–2015, and calculated the number of days per year in which the average ITF was greater than 1°C (ITFD) and the corresponding variance of the ITF (ITFL). The annual average ITFs were mostly warming; the first half of the year experienced mainly warming, while the second half underwent cooling. The level and frequency of the interday maximum temperature fluctuation contributed greatly to increases in the interday mean temperature fluctuation level and frequency. The spatial distributions of ITFD and ITFL were related to their latitude and longitude. Stations with positive ITFD indicator trends were mostly concentrated in the southwestern LPC, while stations with negative ITFL indicator trends mainly occurred in the northwestern LPC. At an 850 hPa geopotential height, the stronger ITFs in spring more strongly correlated with the Mongolian high and Aleutian low. While at a 500 hPa geopotential height, the ITF were more strongly correlated with the Mongolian high. These results suggest that ITFs are more complex than previously reported and may need to be considered in future climate change assessments.